The banjir rescue: an IoT-based flood evacuation center system / Nur Aliah Syamsurial - Syamsurial, Nur Aliah (2020)
One of the important process involves when disaster happens is to allocate the victims to the navigation center. Current evacuation practice may cause further damage as the victims need to wait for the rescuer team to come. Thus, a self-navigation system would allow the victims to save their life and belongings sooner by determining the appropriate evacuation center. In this approach, the appropriate evacuation center is determined based on two critical parameters which are the water level and distance. First, the near-real time data retrieved from water level sensor set up at the evacuation centers is sent to the system and being compared with the evacuation centers’ water threshold value. The algorithm will then proceed with the second phase that is checking for the distance between the victims’ current location and the evacuation center, if the water level found at the first phase is less than the threshold. Finally, the selection is made where the algorithm will choose the nearest evacuation center to the victims. The system will get the coordinates of the appropriate evacuation center that passes both phases and send the coordinates to the installed navigation applications on the mobile phone such as Google Maps and Waze. The desired navigation app will be launched with the coordinates passed from the system to guide victims to reach the appropriate evacuation center. The result shows that the proposed approach could provide a near-real-time water level reading of each sensor and near-accurate distance calculation to the system to determine the appropriate evacuation center.